Excavations at Olynthus. Part VIII: The hellenichouse. A study of the houses found at Olynthus, with a detailed account of those excavated in 1931 and 1934, by David M. Robinson and J. Walter Graham. (=The Johns Hopkins University Studies in ... - Μπ. Γ. (Μακεδονικά, 2017)
[χωρίς περίληψη]